Novel Mutations in Neuroendocrine Carcinoma of the Breast: Possible Therapeutic Targets. Issue 2 (February 2015) - Ang, Daphne; Ballard, Morgan; Beadling, Carol; Warrick, Andrea; Schilling, Amy; O'Gara, Rebecca; Pukay, Marina; Neff, Tanaya L.; West, Robert B.; Corless, Christopher L.; Troxell, Megan L.
Abstract : Primary neuroendocrine carcinoma of the breast is a rare variant, accounting for only 2% to 5% of diagnosed breast cancers, and may have relatively aggressive behavior. Mutational profiling of invasive ductal breast cancers has yielded potential targets for directed cancer therapy, yet most studies have not included neuroendocrine carcinomas. In a tissue microarray screen, we found a 2.4% prevalence (9/372) of neuroendocrine breast carcinoma, including several with lobular morphology. We then screened primary or metastatic neuroendocrine breast carcinomas (excluding papillary and mucinous) for mutations in common cancer genes using polymerase chain reaction-mass spectroscopy (643 hotspot mutations across 53 genes), or semiconductor-based next-generation sequencing analysis (37 genes). Mutations were identified in 5 of 15 tumors, including 3 with PIK3CA exon 9 E542K mutations, 2 of which also harbored point mutations in FGFR family members ( FGFR1 P126S, FGFR4 V550M). Single mutations were found in each of KDR (A1065T) and HRAS (G12A). PIK3CA mutations are common in other types of breast carcinoma. However, FGFR and RAS family mutations are exceedingly rare in the breast cancer literature. Likewise, activating mutations in the receptor tyrosine kinase KDR (VEGFR2) have been reported in angiosarcomas and non–small cell lung cancers; the KDR A1065T mutation is reported to be sensitive to VEGFR kinase inhibitors, and fibroblast growth factor receptor inhibitors are in trials. Our findings demonstrate the utility of broad-based genotyping in the study of rare tumors such as neuroendocrine breast cancer.